Ovarian-ectopic pregnancy: a rare case report - Swethamrutha, Chittari; S. R., Sheela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ovarian ectopic pregnancy (OEP), is one of the variants of the non-tubal ectopic pregnancy, which varies one in 7,000–16,000 deliveries, and its prevalence is 1-3% among ectopic pregnancy. OEP is a complication which occurs when implantation and embryo development happens outside of the uterus. Usually, 91% of OEP terminates with rupture before the end of 1st trimester and it can lead to pregnancy complications such as hemorrhage and hypovolemic shock. Clinical presentation of OEP is lower abdominal or pelvic pain, or both. In addition to this, other symptoms include nausea, vomiting, and constipation. It is one of the life-threatening conditions that cause maternal morbidity and mortality. In this case study we report a 20-year-old primigravida who presented to R. L. Jalappa hospitals emergency department with pain abdomen, with history of 2 months of amenorrhea, unaware of her last menstrual period, on examination her vitals were unstable and left iliac fossa tenderness noted on per abdomen examination, ultrasound showing ruptured ectopic pregnancy, patient was managed successfully through emergency exploratory laparotomy with unilateral oophorectomy.